Tolerance to intimate partner violence in three life his tories of women of high socioeconomic status in Lima (2017)
Objective: This study analyzes the presence of physical and psychological violence by a partner (man) to a victim (woman) in the high socioeconomic status in Lima. Materials and methods: Data were collected through the “life history” technique, in a profound record of the speeches of three adult women of high socioeconomic status. Results: The results confirm deductions from the previous literature (concentrated in sectors of low and medium socioeconomic statuses) in the forms, cycle and tolerance towards violence. This strengthens the argument that the socioeconomic variable is neither a determining variable nor an inhibitor of violence. Discussion: The study shows the forms of violence exercised during the relationship, the mechanisms of domination and control, and the ways in which women tolerated violence over a prolonged period, due not only to the fear of physical reprisals and economic control, but also to the important presence of the discourse on the preservation of family and the care of children in a two-parent structure. Conclusions: The cases confirm previous results according to which physical, psychological and economic violence are often manifested in long and cyclical periods, in which victims and the social environment tolerate violence, despite being recognized as negative, harmful and painful.